The Turn of the Adaptation: Henry James, Daphne Du Maurier and Netflix - Lobato Díez, Paula (Journal of Artistic Creation and Literary Research, 2025)
The present essay aims to unveil underlying connections among Henry James’s The Turn of the Screw (1989), Daphne Du Maurier’s Rebecca (1938) and the Netflix series The Haunting of Bly Manor (2020) which neither the British author’s text nor its creator, Mike Flangan, ever acknowledged. In doing so, this paper sensitively discerns which literary issues from earlier centuries are still relevant and theorizes about the phenomenon of streaming platforms. The two novels are addressed through the works of scholars which coexist with non-academic sources like interviews or even internet blogs. The aim is to bring profiles of spectators who access the show from greatly different backgrounds into focus: erudite avid readers and hardened binge watchers. This work of analysis proves the Netflix series to be an adaptation of James’s work by dissecting the changes it has undergone in order to appeal its audience while appropriating central aspects of Rebecca along the way. By the end of the paper, all three creative works reach a fluent dialogue about the two Rebeccas and their anthitheses. Their worlds slowly become one, channeled through the figure of Viola Willoughby, who merges both stories as an analogy of purgatory be it either at Manderley or Bly.